(untitled) (Ghana Journal of Science, Technology and Development, 2023)
Packaged water is touted as hygienic and safe for human consumption. However, several studies have reported a change in water quality due to some environmental factors. In the case of plastic-packaged drinking water, the water quality may be affected by sunlight due to the possibility of leaching petroleum hydrocarbons from the plastics into the water. Total Petroleum Hydrocarbon (TPH) describes a large family of several chemical compounds that originates from crude oil and are known to cause varied ailments including cancer. The study therefore aimed at elucidating the effect of sunlight on TPH levels, of packaged drinking water sampled in the Tamale Metropolis. In all, sachet water from five different brands was exposed to sunlight for seven days and five-set as control under room temperature. Extraction of the TPH from the sachet water collected was done using liquid-liquid extraction techniques followed by Solid-Phase Extraction purification at the Ghana Standard Authority. Target components were analytically determined with Gas Chromatography-Flame Ionisation Detector (GC-FID) and quantified by the area counts. The total amount of TPH identified ranged from 1.6 ×10 -3 µgl-1 to 2.3×10 -3 µgl-1 in the control water samples whilst that of the exposed water ranged from 2.1×10 -3 µgl-1 to 3.1 ×10 -3 µgl-1. The mean concentration of TPH in exposed samples revealed 25% increase in the TPH levels. Comparing the study to recommendations from the World Health Organisation, TPH must be absent from drinking water hence the sachet water samples are not safe for drinking. There is, therefore, the need for education of vendors and consumers on the safe storage of sachet water for the safety of consumers. Key words: sachet water, quality, sunlight, leaching, Total Petroleum Hydrocarbons.